2020
DOI: 10.3390/foods9060775
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Volatiles and Polyphenol Content, Physicochemical Parameters and Antioxidant Activity in Beers with Dotted Hawthorn (Crataegus punctata)

Abstract: Beer with the addition of dotted hawthorn (Crataegus punctata) fruit and juice was prepared and analysed. The content of carbohydrates, glycerol and ethanol in beers was determined by high-performance liquid chromatography (HPLC). Analysis of the total content of polyphenols was also performed using the Folin-Ciocalteu method, as well as determining antioxidant capacity by DPPH• and ABTS+• assay, and the ability to reduce iron ions by FRAP assay. Content of volatile compounds was analysed by means of solid-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
1
22
1
Order By: Relevance
“…A strong positive correlation was observed between the content of polyphenols (TPC) and the level of browning index expressed in absorbance units (r = 0.93), the ability to reduce iron ions (FRAP) (r = 0.91), antioxidant capacity ABTS •+ (r = 0.75), the content of HMF (r = 0.87) and dextrins (r = 0.82). The influence of polyphenolic compounds on the antioxidant activity has already been demonstrated many times [ 26 , 27 , 28 , 29 ]. The analysis showed significant correlation between the results of the antioxidant capacity test with the ABTS •+ and FRAP methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong positive correlation was observed between the content of polyphenols (TPC) and the level of browning index expressed in absorbance units (r = 0.93), the ability to reduce iron ions (FRAP) (r = 0.91), antioxidant capacity ABTS •+ (r = 0.75), the content of HMF (r = 0.87) and dextrins (r = 0.82). The influence of polyphenolic compounds on the antioxidant activity has already been demonstrated many times [ 26 , 27 , 28 , 29 ]. The analysis showed significant correlation between the results of the antioxidant capacity test with the ABTS •+ and FRAP methods.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of various types of beers and main raw materials used for their production has been repeatedly described in the literature. The influence of the addition of various malts, hops, fruits or fruit juices and their application on the physicochemical parameters and the sensory profile of beer have also been studied [ 23 , 24 , 25 , 26 , 27 , 28 ]. Additionally, it has been shown that dark beers possess a considerably higher content of polyphenols and antioxidative activity than pale beers [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the latest research, beers' physicochemical analysis has been mainly based on the bioactive compounds in craft beers [1], volatiles, and antioxidant properties when adding fruit using gas chromatography/mass-spectroscopy (GC-MS) and high-performance liquid chromatography (HPLC) [1][2][3]. Many other studies coupled these analyses of quality traits with sensory trials when analyzing processes to change beer characteristics, such as ultrasound-assisted thermal processing [4], antioxidant activity through natural additives [5][6][7], for sweet potato beers [8] and commercial beers [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the second topic of studies of different processing and conditions, six manuscripts have been published [ 4 , 5 , 6 , 7 , 8 , 9 ]. The authors provide an overview of recent advances made in the field of food processing establishing the best processing conditions in order to obtain food based products with a high quality in terms of aroma, flavor and, consequently, consumer satisfaction.…”
mentioning
confidence: 99%
“…The same authors claim that still this novel confectionary product must be improved and propose further investigations related to (i) hydrating gelatin in pomegranate juice instead of water and (ii) optimizing the drying step. The third study by Gasinski et al [ 6 ] performed an assessment of volatile compounds among other determinators of beers enriched with dotted hawthorn ( Crataegus punctate ) by two ways of addition, fruit or juice. The study indicated that the addition of hawthorn led to a beer with an increased total content of polyphenolic compounds and antioxidant activity.…”
mentioning
confidence: 99%